Pediatric Digestive Surgery - Lima, Mario; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents and explains the latest developments in surgery for congenital digestive tract malformations, tumors, abdominal trauma, and the most important acquired digestive disorders. Particular attention is paid to minimally invasive and innovative techniques. In addition to clear descriptions of the surgical procedures that highlight useful tips and tricks, for each condition the clinical presentation is well illustrated and information is provided on pathogenesis. The book also includes general chapters that address the anatomy of the abdomen in children, diagnostic issues, the problem of clinical nutrition, and other aspects of management in pediatric patients with gastrointestinal pathologies. Pediatric Digestive Surgery will serve as a comprehensive and up-to-date reference for all pediatric surgeons. It will provide the trainee with easily understood, concise guidance while offering the more experienced surgeon valuable updates on the latest thinking and practice in the field.
Preface -- Prenatal Diagnosis and Obstetric Management -- Digestive Radiology -- Diagnostic and Therapeutic Endoscopy -- Anesthesia in Digestive Surgery -- Intensive Care in Digestive Surgery -- Clinical Nutrition -- Vascular Rings -- Congenital Esophageal Stenosis -- Achalasia and Esophageal Motility Disorders -- Laringotracheoesophageal Cleft -- Esophageal Atresia and Tracheo-Esophageal Fistula -- Hiatal Hernia and Gastro-esophageal Reflux -- Esophageal Replacement -- Pyloric Stenosis -- Congenital Duodenal Stenosis -- Caustic Ingestion and Foreign Bodies -- Intestinal Malrotation -- Alimentary Tract Duplications -- Meckel Diverticulum -- Acute Appendicitis -- Intussusception -- Hirschsprung Disease -- Inflammatory Bowel Diseases -- Anorectal Malformations -- Nesidioblastosis -- Hepatobilio Pancreatic Pathology -- Portal Hypertension -- Short Bowel Syndrome -- Intestinal Polyposis -- Tumours -- Augmented Reality in Digestive Surgery -- Subject Index.
Keywords: Medicine; Abdominal surgery; Minimally invasive surgery; Pediatric surgery; Medicine & Public Health; Pediatric surgery; Minimally invasive surgery; Abdominal surgery